1993
DOI: 10.7164/antibiotics.46.11
|View full text |Cite
|
Sign up to set email alerts
|

Tetronothiodin, a novel cholecystokinin type-B receptor antagonist produced by Streptomyces sp. NR0489. II. Isolation, characterization and biological activities.

Abstract: A novel cholecystokinin type-B receptor antagonist named tetronothiodin has been isolated by column chromatography and preparative HPLCfrom the fermentation broth of Streptomyces sp. NR0489. Tetronothiodin inhibited the binding of CCK8(C-terminal octapeptide of cholecystokinin) to rat cerebral cortex membranes (CCK type-B receptors) with an IC50 of 3.6nM, whereas it did not inhibit CCK8binding to rat pancreatic membranes (CCK type-A receptors). It also inhibited CCK8induced Ca2+ mobilization in GH3cells, a rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…Yoshii and coworkers reported the chemical synthesis of (+)-tetronolide, the aglycone of tetrocarcin (5), in 1991. 25 Enantioselective synthesis of (−)-chlorothricolide, the aglycone of chlorothricin (4), was accomplished by Roush and Sciotti in 1994. 26 Both syntheses employed intramolecular DielsAlder cyclizations to construct the spirotetronate and octahydronaphthalene portions of the aglycones.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yoshii and coworkers reported the chemical synthesis of (+)-tetronolide, the aglycone of tetrocarcin (5), in 1991. 25 Enantioselective synthesis of (−)-chlorothricolide, the aglycone of chlorothricin (4), was accomplished by Roush and Sciotti in 1994. 26 Both syntheses employed intramolecular DielsAlder cyclizations to construct the spirotetronate and octahydronaphthalene portions of the aglycones.…”
mentioning
confidence: 99%
“…Kijanolide has not yet been chemically synthesized, but the preparation of an advanced seco-acid intermediate was recently reported. 27 Biosynthetic studies of chlorothricin (4) have been performed by Floss and coworkers. 28 Through feeding of labeled acetate and propionate, it was found that the chlorothricolide aglycone (6) is primarily polyketide-derived, except for C22-C24 which are uniformly labeled after feeding of [ 13 C 3 ]-glycerol ( Figure 1).…”
mentioning
confidence: 99%
“…NR0489. 280,281 This compound inhibited the CCK-8 binding to rat cerebral cortex membranes with nanmolar binding affinity, whereas it did not showed affinity at rat pancreatic membranes. It also inhibited the CCK-8-induced Ca 2 þ mobilization in rat anterior pituitary cells GH3, but it did not inhibit the basal cytosolic Ca 2 þ concentration.…”
Section: Tetronothiodinmentioning
confidence: 95%
“…It also inhibited the CCK-8-induced Ca 2 þ mobilization in rat anterior pituitary cells GH3, but it did not inhibit the basal cytosolic Ca 2 þ concentration. 280 …”
Section: Tetronothiodinmentioning
confidence: 97%
“…Chiral tetrahydrothiophene‐based compounds include the water‐soluble B vitamin biotin ( 1 ), involved in important biological functions, and the potent α‐glucosidase inhibitors salacinol ( 2 ) and kotalanol ( 3 ), isolated from several Salacia species (Scheme ). Further typical compounds are the 4′‐thioadenosine derivative 4 , a highly effective and selective A3 adenosine receptor antagonist, the cholecystokinin type‐B receptor antagonist tetronothiodin ( 5 ), the 4′‐thiocytidine nucleoside 6 , active against HSV‐1 and HSV‐2, and ( R )‐tetrahydrothiophen‐3‐ol ( 7 ), an essential intermediate en route to the potent antibacterial Sulopenem ( 8 ; Scheme ) . Furthermore, tetrahydrothiophenes have also been employed as building blocks for new chiral ligands in various chemical transformations including asymmetric hydrogenation, catalytic asymmetric epoxidation and catalytic intramolecular cyclopropanation .…”
Section: Introductionmentioning
confidence: 99%